Analysis of technical-tactical actions in high-level table tennis players: Differences between sexes - Pradas de la Fuente, F.; Ortega-Zayas, M.Á.; Toro-Román, V.; Moreno-Azze, A. (Sports, 2023)
Table tennis is a sport played at a high speed; therefore, the technical-tactical variables are very important. The objective of the research is to analyze the technical and tactical characteristics of high-level TT players according to sex. A total of 48 high-level players (24 women and 24 men) participated in the present study. The investigation was carried out during two championships. The matches were recorded and subsequently analyzed by notational analysis. The results indicate that women stroke the ball more times during the rallies. In the men`s competition, the forehand technique predominates over the backhand technique. The flip was the most used in the male sex (p < 0.05). At the tactical level, more winning actions were performed in the men`s competition than in the women`s, both with the forehand and backhand game. Men performed more losing technical actions when using the forehand and backhand flips. The pivot footwork tactical action was higher in the men`s competition. The analysis of the technical-tactical actions highlighted important differences between the sexes. The predominant losing techniques among players are forehand and backhand flip. Female players use more defensive strokes, while male players use more offensive strokes, in particular the flip technique. The potential biomechanical progress of the male player characterized by a larger wingspan biotype could facilitate a better technical-tactical performance. The results obtained are of interest to improve the performance of the players as they must train at a technical-tactical level differently depending on the sex and style of play.